2023
DOI: 10.1097/inf.0000000000003990
|View full text |Cite
|
Sign up to set email alerts
|

Unique Immune Blood Markers Between Severe Dengue and Sepsis in Children

Abstract: Background: Pediatric dengue and sepsis share clinical and pathophysiologic aspects. Multiple inflammatory and regulatory cytokines, decoy receptors and vascular permeability factors have been implicated in the pathogenesis of both diseases. The differential pattern and dynamic of these soluble factors, and the relationship with clinical severity between pediatric dengue and sepsis could offer new diagnosis and therapeutic strategies. Methods: We evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…These data are in line with our recent study, where we observed upregulation of IL-6 in children with dengue plus bacterial sepsis, relative to individuals with sepsis alone. 51 In the clinical setting, IL-6 measurement (in addition to other clinical and laboratory parameters) could help to better guide the early diagnosis of these concomitant entities.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in line with our recent study, where we observed upregulation of IL-6 in children with dengue plus bacterial sepsis, relative to individuals with sepsis alone. 51 In the clinical setting, IL-6 measurement (in addition to other clinical and laboratory parameters) could help to better guide the early diagnosis of these concomitant entities.…”
Section: Discussionmentioning
confidence: 99%
“…A modo de conclusión, es posible indicar que la combinación 11 del estudio comprendía una proteína C reactiva negativa y plaquetopenia fue lo más relevante en el estudio, y presentó mayor validez como posible herramienta para el diagnóstico (20)(21)(22)(23)(24) . Por ello se considera una opción atractiva para el diagnóstico presuntivo de dengue en la sala de urgencias en la que el paciente fue recibido.…”
Section: Comounclassified